2011
DOI: 10.1152/japplphysiol.01021.2010
|View full text |Cite
|
Sign up to set email alerts
|

Muscle damage alters the metabolic response to dynamic exercise in humans: a31P-MRS study

Abstract: We used ³¹P-magnetic resonance spectroscopy to test the hypothesis that exercise-induced muscle damage (EIMD) alters the muscle metabolic response to dynamic exercise, and that this contributes to the observed reduction in exercise tolerance following EIMD in humans. Ten healthy, physically active men performed incremental knee extensor exercise inside the bore of a whole body 1.5-T superconducting magnet before (pre) and 48 h after (post) performing 100 squats with a load corresponding to 70% of body mass. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 56 publications
4
21
1
Order By: Relevance
“…Blood lactate levels have also been shown to be elevated (Burt et al, 2013;Gleeson et al, 1998Gleeson et al, , 1995 following EIMD-suggesting a greater reliance on anaerobic metabolism may occur in the undamaged muscle fibers. This is further supported by the finding of an increased ratio of inorganic phosphate (P i ) to phosphocreatine (PCr) (Davies et al, 2011a;Foure et al, 2014) in resting muscle. Our finding of a prolonged reduction of GET would be consistent with greater metabolic stress on undamaged fiber and could lead to an earlier onset of lactate accumulation, fatigue, and consequently a reduced V˙ O 2peak .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Blood lactate levels have also been shown to be elevated (Burt et al, 2013;Gleeson et al, 1998Gleeson et al, , 1995 following EIMD-suggesting a greater reliance on anaerobic metabolism may occur in the undamaged muscle fibers. This is further supported by the finding of an increased ratio of inorganic phosphate (P i ) to phosphocreatine (PCr) (Davies et al, 2011a;Foure et al, 2014) in resting muscle. Our finding of a prolonged reduction of GET would be consistent with greater metabolic stress on undamaged fiber and could lead to an earlier onset of lactate accumulation, fatigue, and consequently a reduced V˙ O 2peak .…”
Section: Discussionmentioning
confidence: 80%
“…The disruption of sarcomere and contractile ultrastructure following EIMD leads to a well characterized sequelae of signs and symptoms including elevated serum creatine kinase (Newham et al, 1983a), inflammation and localized edema (Black et al, 2008;Black and McCully, 2008a), a decreased ability to generate force (Newham et al, 1983b), and heightened pain sensitivity-often termed delayed-onset muscle soreness (DOMS) (Newham et al, 1983b). A growing body of evidence clearly indicates EIMD negatively impacts endurance exercise performance as demonstrated by reductions in time-trial performance (Burt and Twist, 2011;Marcora and Bosio, 2007;Twist and Eston, 2009) and time-toexhaustion (Asp et al, 1998;Carmichael et al, 2006Carmichael et al, , 2010Davies et al, 2011aDavies et al, , 2008Davies et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the typical inflammation response to voluntary EIMD has been associated with an increased metabolic rate at rest (10), which is likely to result from repair and remodeling processes of muscular tissues, thereby requiring energetically demanding protein synthesis (49). 31P magnetic resonance spectroscopy (jI P-MRS) studies have consistently reported a higher resting inorganic phosphate (Pi)/phosphocreatine (PCr) ratio after voluntary eccentric EIMD (9,37,41). This higher [Pi]/[PCr] ratio might account for impaired exercise tolerance (i.e., reduced time to exhaustion) after volun tary eccentric EIMD (9).…”
mentioning
confidence: 99%
“…31P magnetic resonance spectroscopy (jI P-MRS) studies have consistently reported a higher resting inorganic phosphate (Pi)/phosphocreatine (PCr) ratio after voluntary eccentric EIMD (9,37,41). This higher [Pi]/[PCr] ratio might account for impaired exercise tolerance (i.e., reduced time to exhaustion) after volun tary eccentric EIMD (9). However, the adenosine diphosphate (ADP) recovery rate was not affected by the voluntary eccen tric EIMD in the latter study, thereby suggesting that mito chondrial alterations previously reported in vitro (13) did not translate into similar changes in vivo.…”
mentioning
confidence: 99%